Complete paraparesis following resection of parasagittal meningioma: recovering function with an early intensive neurorehabilitation program - Mazlan, M.; Fauzi, A.A. (2011)
Paraparesis can occur as a primary presentation of brain pathology at the motor strip along the parasagittal region. It could also occur as a neurological complication especially following resection of parasagittal meningioma with infiltration of the superior sagittal sinus (SSS). We report a case of a complete paraparesis immediately following resection of bilateral parasagittal meningioma with infiltration of the middle third of the SSS. A gradual improvement in neurological recovery and functional outcome was observed over a period of one year after undergoing an intensive neurorehabilitation program beginning from the acute inpatient phase post surgery.